Menggunakan Karunia Rohani Sebagai Bentuk Membangun Iman Jemaat Analisa Teks (1 Korintus 14:26-40) - Adolfitri Bella; Herlince Rumahorbo (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
Encouraged by the motivation of serving His congregation in Corinth, through the Apostle Paul, Godâ€™s servant who was entrusted with establishing, guiding, and advising Godâ€™s people there in Godâ€™s word which reads : â€œThough I have the gift of prophecy and know all mysteries and have all knowledge; and though I have faith perfect to move mountains, yet I have no love, I am utterly uselessâ€ (TB 1 Cor 13:2). So, with the motivation because I love God's congregation, who have mistaken the spiritual gifts that God has bestowed or have wrong perceptions, I wrote a paper with the title "Using spiritual gifts as a form of building congregations", so that we all know that the gifts that are God gives is to have noble intentions and goals.